The governance of corporate groups - Dine, Janet (Cambridge studies in corporate law., 2000)
This book explores the legal issues concerning groups of companies including regulation at national, international and global level. It offers a comparative discussion of the way in which these issues have been approached in the UK, in the EU and the eastern European states, and in the US.